Evaluation of errors in determination of DNA melting curve registered with differential scanning calorimetry - D. Y. Lando; I. E. Grigoryan; A. S. Fridman; E. N. Galyuk; Y. B. Dalyan; S. G. Haroutiunian (ՀՀ ԳԱԱ հրատ.)
The differential scanning calorimetry (DSC) is more sensitive than UV absorption spectrophotometry as a tool for the measurement of DNA melting curves. The advantage of DSC is a direct determination of differential melting curves (DMC) obtained without numerical differentiation.ԴՆԹ-ի հալման կորերի ստացումը դիֆերենցիալ սկանավորող կալորիմետրի (ԴՍԿ) միջոցով ավելի ճշգրիտ է քան` ՈւՄ սպեկտրոֆոտոմետրի միջոցով: ԴՍԿ-ի առավելությունը կայանում է հալման դիֆերենցիալ կորերի (ՀԴԿ) ուղղակիորեն որոշման մեջ, առանց թվային դիֆերենցման: Измерение кривых плавления ДНК методом дифференциальной сканирующей калориметрии (ДСК) является более точным, чем при использовании УФ-спектрофотометрии. Преимуществом ДСК является прямое определение дифференциальных кривых плавления (ДКП), получаемых без численного дифференцирования.
Keywords: Biology; Biophysics